Islamic Education Management Strategies for Improving Learning Quality in Islamic Boarding Schools - Hadi Mulyo Wibowo (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study investigates strategies for improving the quality of learning in Islamic boarding schools through effective Islamic education management, innovative curriculum development, and comprehensive teacher professional development. Islamic boarding schools have long served as vital institutions in nurturing students’ moral, spiritual, and intellectual character, yet many continue to face challenges related to traditional management systems, rigid curricula, and limited teacher training opportunities. The purpose of this research is to identify adaptive management and pedagogical strategies that can align Islamic boarding schools’ education with contemporary educational standards while maintaining core Islamic values. Employing a qualitative library research design, this study analyzes scholarly literature, academic journals, and policy reports using content analysis techniques to uncover theoretical insights and best practices in Islamic education management. The findings reveal that enhancing learning quality in Islamic boarding schools requires modernization of management systems, integration of religious and general knowledge in the curriculum, and sustained investment in teacher capacity-building. Effective leadership, curriculum innovation, and continuous professional development collectively foster a dynamic and high-quality learning environment. The study concludes that the integration of modern educational approaches with Islamic principles is essential for strengthening Islamic boarding schools’ institutional performance, improving student learning outcomes, and ensuring their continued relevance in the modern educational landscape.